Composite cubic Bézier surface with Cr continuity - Cheah, Seong Leang * (Sunway University College, 2006)
The Bézier surface with Cr continuity on each common boundary between two composite triangular Bézier patches is generated. The directional derivatives on the Bernstein polynomials are discussed. This is to ensure that the Cr continuity is maintained along the boundary between the piecewise polynomials. The composite patches are then generated by elevating the degree of the Bézier triangles.